Front Cover: Structural stratification of Sr1 − xCaxRuO3 thin films: Influence of aging process (Phys. Status Solidi A 2/2013). Issue 2 (15th February 2013) - Młynarczyk, Marcin; Szot, Krzysztof; Poppe, Ulrich; Breuer, Uwe; Mi, Shaobo; Psiuk, Bronisław; Görlich, Edward A.; Tomala, Krzysztof; Waser, Rainer
<x xml:space="preserve">Abstract</x> Ruthenates represent an attractive field of investigation both due to their physical properties (electric conductivity, superconductivity, magnetism – often unconventional) and for their possible technical applications. The heterogeneous in‐depth profile of the thin films is extremely important in the fabrication of nanodevices, especially those based on ultra‐thin layers. Młynarczyk et al. (pp. 239–254) systematically investigate structural features of epitaxial Sr1 − xCaxRuO3 thin films grown on SrTiO3 and LaAlO3 substrates with the use of high‐pressure dc‐sputtering. The series of samples were characterized with a number of complementary methods: X‐ray diffraction, Rutherford back‐scattering, high‐resolution transmission electron microscopy, time‐of‐flight secondary ion mass spectrometry, atomic force microscopy, and X‐ray photoemission spectroscopy were used to characterize both in‐depth and lateral structure features. Possible applications of Sr1 − xCaxRuO3 thin films are largely determined by their thermal and chemical instability. Excessive process of aging was observed for the samples prepared with high pressure dc‐sputtering stored under normal conditions. Progressive stoichiometry instability at the surface layer in a presence of adsorbates should be noted as it significantly limits potential applications of these thin films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>